Quality of service in mobile IP networks with parametric multi-channel routing algorithms based on linear programming approach - Gholizadeh, Somayyeh (2018)
Quality of service (QoS) is an essential consideration and an open challenge in computer networking. Providing QoS guarantees becomes even more challenging when the complexities of mobile IP networks are taken into account. In a Mobile IP Network, when a node moves, it may go away from other nodes, this node movement decreases the available bandwidth, reduces the data transmission rate and increases the propagation delay. These issues affect the network efficiency and make a significant reduction in Mobile IP network performance and utilization. In other words, uncontrolled node movements in a Mobile IP network cause network failure, and nonoptimized mobile node movements from a Foreign Network to another Foreign Network lead to an increase in handoff latency. This work is going to improve network efficiency to guarantee QoS in Mobile IP Network by increasing data transmission rate, avoiding communication failure, and reducing handoff latency. The proposed work has been used to optimize data transmission rate by controlling the node movements and node shiftings in a limited domain, avoid communication failure by preventing nodes from exiting their domain and reduce the handoff latency in Mobile IP networks. In the proposed approaches, to overcome the mentioned issues in Mobile IP networks when a Mobile Node moves, parametric linear programming and graph theory are employed. To achieve mobility control in Mobile IP networks, a new linear programming formulation for guaranteeing the optimality of data transmission and network connectivity is proposed. This approach tunes the parameters of the linear programming models that are used in the other algorithms by using a dynamic element. The proposed algorithms are evaluated by considering different metrics, computation modellings, and measurements on the simulation. The simulation results reveal noticeable data transmission rate improvement over previous routing approaches by optimizing the linear programming models. The proposed node movement control algorithm achieves a 31 percent improvement compared to HMIP and FMIP. Furthermore, Optimized Parametric Topology Control Routing algorithm performs significantly better than Triangular Routing Method and Change Foreign Agent Algorithm. The simulation results show the improvement is about 50 percent reduction of handover latency in different Mobile IP network scenar ios.